Pengaruh Return On Equity, Debt To Equity Ratio, Dan tumbuhan Aset-Aset Terhadap Return Saham Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014 - Komah, Astrea Esti; , Drs. Agus Muqorobin,MM (2017)
This research aims to influence Debt To Equity Ratio (DER), Return on Equity (ROE), and Asset Growth. The object of this research is on company property and real estate Listed in Indonesia Stock Exchange Year 2011-2014. Sample companies represented 44 property companies and real estate. The data as a whole amounted to 176 data. Data used after dioutlier many as 141 data. This analysis using SPSS with classic assumption test, and Regression Analysis. The findings indicate that partially and simultaneously both Debt To Equity Ratio (DER), Return on Equity (ROE), and the growth of assets under common significant influence to return.